Highly sensitive NO2 sensor using brush-coated ZnO nanoparticles - Chandra L.; Dwivedi R.; Mishra V.N. (My University, 2025)
This work reports the sensing properties of a ZnO nanoparticle (NP) based gas sensor. A sol-gel method was used for the synthesis of ZnO nanoparticles, and a brush coating technique for applying these in a thick film over the gold electrode. The structural properties of the ZnO film so developed have been studied using energy dispersive x-ray spectroscopy (EDS), x-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM), revealing a hexagonal wurtzite structure having particle size of ∼25 to ∼110 nm and roughness of ∼136.303 nm. The sensitivity of the sensor to NO2, H2, CO, ethanol and propanol gases in the temperature range from 150 to 350 °C has been tested. Among all these gases, sensitivity to NO2 was found to be highest, at around fifty times greater than the next highest sensitivity, for ethanol gas. The sensor's response to NO2 gas has been measured at ∼945.12%/ppt (parts per thousand), with fast response time and recovery time at operating temperature 280 °C. The obtained result has been discussed with the help of surface and subsurface adsorption and desorption of NO2 molecules at the available trap sites (oxygen ions) on the ZnO nanoparticle surface. This sensor also exhibits excellent repeatability. © 2017 IOP Publishing Ltd.